Medication Costs by Glucose Tolerance Stage in Younger and Older Women and Men: Results from the Population-based KORA Survey in Germany - Claessen, H.; Strassburger, K.; Tepel, M.; Waldeyer, R.; Chernyak, N.; Jülich, F.; Albers, B.; Bächle, C.; Rathmann, W.; Meisinger, C.; Thorand, B.; Hunger, M.; Schunk, M.; Stark, R.; Rückert, I. M.; Peters, A.; Huth, C.; Stöckl, D.; Giani, G.; Holle, R.; Icks, A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To estimate medication costs in individuals with diagnosed diabetes, undetected diabetes, impaired glucose regulation and normal blood glucose values in a population-based sample by age and sex.Using the KORA F4 follow-up survey, conducted in 2006–2008 (n=2611, age 40–82 years), we identified individuals’ glucose tolerance status by means of an oral glucose tolerance test. We assessed all medications taken regularly, calculated age-sex specific medication costs and estimated cost ratios for total, total without antihyperglycemic drugs, and cardiovascular medication, using multiple 2-part regression models.Compared to individuals with normal glucose values, costs were increased in known diabetes, undetected diabetes and impaired glucose regulation, which was more pronounced in participants aged 40–59 years than in those aged 60–82 years (cost ratios for all medications: 40–59 years: 2.85; 95%-confidence interval: 1.78–4.54, 2.00; 1.22–3.29 and 1.53; 1.12–2.09; 60–82 years: 2.04; 1.71–2.43, 1.17; 0.90–1.51 and 1.09; 0.94–1.28). Compared to individuals with diagnosed diabetes, costs were significantly lower among individuals with impaired glucose regulation across all age and sex strata, also when antihyperglycemic medication was excluded (40–59 years: 0.60; 0.36–0.98, 60–82 years: 0.74; 0.60–0.90; men: 0.72; 0.56–0.93; women: 0.72; 0.54–0.96).We could quantify age- and sex-specific medication costs and cost ratios in individuals with diagnosed diabetes, undetected diabetes and impaired glucose regulation compared to those with normal glucose values, using data of a population-based sample, with oral glucose tolerance test-based identification of diabetes states. These results may help to validly estimate cost-effectiveness of screening and early treatment or prevention of diabetes.
Keywords: drug costs; glucose tolerance status; age-sex-strata; population-based survey